33=6+3h

Simple and best practice solution for 33=6+3h equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 33=6+3h equation:


Simplifying
33 = 6 + 3h

Solving
33 = 6 + 3h

Solving for variable 'h'.

Move all terms containing h to the left, all other terms to the right.

Add '-3h' to each side of the equation.
33 + -3h = 6 + 3h + -3h

Combine like terms: 3h + -3h = 0
33 + -3h = 6 + 0
33 + -3h = 6

Add '-33' to each side of the equation.
33 + -33 + -3h = 6 + -33

Combine like terms: 33 + -33 = 0
0 + -3h = 6 + -33
-3h = 6 + -33

Combine like terms: 6 + -33 = -27
-3h = -27

Divide each side by '-3'.
h = 9

Simplifying
h = 9

See similar equations:

| 4e+6=-50-4e | | 5x+3y=182 | | 8+3e=6+e | | 6a+2=7a-1 | | 3e-2=13e-62 | | 9-8g=31 | | -x-8=4x-38 | | xy+2x=300 | | -4-8x+9x=12 | | .33x+10=0.6 | | -6+3y=-15 | | 3e+16=13e-94 | | (2cosx+1)(cosx+1)=0 | | -x^2-4x+32.01=0 | | 60p+50= | | 7u=4u+9 | | (X+7)(x+1)=(x+1) | | 35=-4d+7 | | (x-0.3)+(2x-0.2)+((40+x)-0.25)=274 | | -10(X+1)=8 | | -6x+15=-33 | | 3x-5(x-4)=-8+3x+3 | | 4x-8=4x+-5 | | 45+4x+7+57x=8 | | 2c-4=c+2 | | 4(3x-2)+4(x+1)=100 | | 7a+2a=18-9 | | 2=-3c+26 | | 3x+8x+4=12x+2 | | 8a+10=82 | | 2x+3-2(x-2)=-3(x+1)+22 | | 8n^2+8n=160 |

Equations solver categories